Analysis of Pooled Phase 3 Safety Data for Delafloxacin in Acute Bacterial Skin and Skin Structure Infections. (8th April 2019) - Bassetti, Matteo; Hooper, David; Tillotson, Glenn
Abstract: Background: Through improved understanding of the structure-activity relationship attributes of fluoroquinolones, molecule development has improved efficacy, safety, and tolerability of the class. Adverse events (AEs) associated with the fluoroquinolones are well defined and a prospective part of the development process. However, not all fluoroquinolones have the same AE profile with different substitutions on the core molecule resulting in differences in side effects and spectrum of activity. Unique structural attributes of delafloxacin (DLX) may differentiate its AE profile compared to other fluoroquinolones. This analysis compared the incidence of AEs between DLX and vancomycin/aztreonam across two phase 3 ABSSSI studies in order to provide a broader overview of DLX safety. Methods: Safety events occurring in all subjects in the pivotal phase 3 trials were pooled to provide a broad overview of DLX safety. Results: DLX was safe and well-tolerated in the pooled phase 3 ABSSSI trial population of 741 subjects. Treatment-emergent AEs (TEAEs) were seen in the DLX group versus the comparator group at 45.1% and 47.7%, respectively. Most were mild or moderate in severity. Treatment-related TEAEs were reported in the DLX group versus the comparator group at rates of 22.1% and 26.1%, respectively. Conclusions: Available data show DLX is well tolerated in both intravenous and oral formulation for the treatment of ABSSSI and does not appear to be associated with increased risk of AEs associated with other fluoroquinolones. It remains important to monitor for potential AEs that have been observed with other fluoroquinolones.